Enantioselective Intramolecular Dearomative Lactonization of Naphthols Catalyzed by Planar Chiral Iodoarene - Wang, Yang; Zhao, Cun-Yuan; Wang, Yi-Ping; Zheng, Wen-Hua (Synthesis, 2019)
A series of planar chiral iodoarenes based on [2.2]paracyclophane was synthesized. An efficient asymmetric intramolecular oxidative lactonization of naphthols enabled by a combination of these chiral iodoarenes and mCPBA as oxidant is reported. This reaction proceeds under mild conditions, allowing the formation of spirolactones bearing a tetrasubstituted stereocenter in moderate yields and good enantioselectivity.
Keywords: hypervalent iodine catalysis; [2.2]paracyclophane; planar chirality; asymmetric dearomatization; oxidative lactonization